(untitled) (Andamios, Revista de Investigación Social, 2014)
The article takes the item andamio (scaffold), which appears in the title of the magazine, which to go all over the description of this type by the main general dictionaries of the Spanish language. Subsequently collects new information provided by some of the Spanish corpus, preferably RAE’s Corpes XXI; continues with frequent combinations, provided by applications, such as those Corpes XXI and Sketchengine tools offer; Grammar is the last query to refine the plural andamios which is often used; it is the last search for new information using historical data. The findings highlight the need for a new approach to lexical dictionaries of the Spanish language.